Play and autism: a case study of the role of play for students with Autism Spectrum Disorders - Makri, Konstantina (2013)
Supporting children with autism to develop their skills and abilities may turn out to be quite a challenging task (Nind, 2000). Although a variety of different interventional approaches has been proposed (Mastrangelo, 2009), there is currently a growing interest in the importance of play as a medium of enhancing their social and emotional development (Thomas and Smith, 2004). The purpose of this study is to understand the role of play in the educational provision of children with autism and explore the ways their social, emotional and behavioural development can be affected through a playful environment. To investigate this issue, the case of a single student with autism was thoroughly examined, through both observations as well as interviews. The results showed that play activities offered the student the opportunity to practise his communication skills while initiating social interactions with adults, to enhance his play skills, to reduce his obsessive behaviours as well as to learn to identify his needs and emotions. Although the findings cannot be generalised (Thomas, 2011), they indicate that play may be an important tool for enhancing all areas of development (Mastrangelo, 2009). Implications for future are discussed, suggesting how teachers can enhance children’s with autism play skills while incorporating play in their daily schedule.